The Development of a Box Rebounder Tool as a Media for Training Basic Passing and Controlling Techniques in Football - Dani Alfa Sumitra; Abdul Hakim Siregar; Sanusi Hasibuan; Indra Kasih (Randwick International of Education and Linguistics Science Journal, 2023)
This study aims to develop a box rebounder tool as a training medium for basic passing and controlling techniques. The research was conducted in April 2023. The research location was at SSB Cemerlang Sidodadi Ramunia and SSB Kualanamu. The research subjects in this study were 10 people for small group trials and 20 people for. This research method is research development (R & D). In the small group trial of the athlete subject, a score of 540 was obtained with a percentage of 77.14% (valid) meaning that the product of the development of the box rebounder tool for passing and control techniques is valid. In the small group trial of the training subjects, a score of 61 was obtained with a percentage of 81.33% (valid) meaning that the product of the development of the box rebounder tool for passing and control techniques is valid. In the trial of the large group of athlete subjects, a score of 1204 was obtained with a percentage of 86% (valid) meaning that the product of the development of the box rebounder tool for passing and control techniques is valid. And for testing large groups of training subjects, a score of 211 was obtained with a percentage of 93.78% (valid) meaning that the product of the development of the box rebounder tool for passing and control techniques is valid. So it can be concluded that the development of the Rebounder Box Tool as a Media for Training the Basic Techniques of Passing and Controlling in Football is considered valid (successful).